The effects of cross-hemispheric dorsolateral prefrontal cortex transcranial Direct Current Stimulation (tDCS) on task switching - Leite, Jorge (2013)
Background: Task switching, defined as the ability to flexibly switch between tasks in the face of goal shifting, is a central mechanism in cognitive control. Task switching is thought to involve both prefrontal cortex (PFC) and parietal regions. Our previous work has shown that it is possible to modulate set shifting tasks using 1 mA tDCS on both the left dorsolateral prefrontal cortex and the left primary motor area. However, it remains unclear whether the effects of PFC tDCS on task switching are hemisphere-dependent.Objectives: We aimed to test the effects of three types of cross-hemispheric tDCS over the PFC (left anode right cathode [LA-RC], left cathode right anode [LC-RA] and sham stimulation) on participants' performance (reaction time) and accuracy (correct responses) in two task-switching paradigms (i.e., letter/digit naming and vowel-consonant/parity tasks).Methods: Sixteen participants received cross-hemispheric tDCS over the PFC in two task-switching paradigms.Results: The results show that cross-hemispheric tDCS over the PFC modulates task-switching ability in both paradigms. Our results were task and hemisphere-specific, such that in the letter/digit naming task, LA-RC tDCS increased switching performance, whereas LC-RA tDCS improved accuracy. On the other hand, in the vowel-consonant/parity task, LA-RC improved accuracy, and decreased switching performance.Conclusions: Our findings confirm the notion that involvement of the PFC on task switching depends critically on laterality, implying the existence of different roles for the left hemisphere and the right hemisphere in task switching.